A microRNA profile of the saliva in the argasid ticks Ornithodoros erraticus and Ornithodoros moubata and prediction of specific target genes - Ana Laura Cano-Argüelles; Ricardo Pérez-Sánchez; Ana Oleaga (Ticks and Tick-Borne Diseases, 2023)
Ornithodoros erraticus and Ornithodoros moubata ticks are the main vectors of the agents of human relapsing fever (TBRF) and African swine fever (ASF) in the Mediterranean Basin and Africa, respectively. Tick ​​saliva is crucial for complete tick feeding and pathogen transmission, as it contains numerous molecules such as proteins, lipids, and non-coding RNAs (ncRNA) including microRNAs (miRNA). MiRNAs are small ncRNAs capable of regulating the expression of their target messenger RNA (mRNA) leading to degradation or inhibition of its translation into protein. Research on miRNAs from ixodid ticks has revealed that miRNAs are involved in the regulation of different physiological processes of ticks, as well as in the modulation of host gene expression, immune response to tick bite and pathogen transmission. Regarding argasid ticks, there is not information about their miRNAs or their potential involvement in tick physiology and/or in the regulation of the tick-host-pathogen interactions. The aim of this work was to profile the miRNAs expressed in the saliva of O. erraticus and O. moubata, and the in silico prediction and functional analysis of their target genes in the swine host. As a whole, up to 72 conserved miRNAs families were identified in both species: 35 of them were shared and 23 and 14 families were unique to O. erraticus and O. moubata, respectively. The most abundant miRNAs families were mir-1, mir-10 and let-7 in O. erraticus and let-7, mir-252, mir-10 in O. moubata. Four miRNAs sequences of each species were validated by RT-qPCR confirming their presence in the saliva. Target gene prediction in the host (Sus scrofa) and functional analysis showed that the selected miRNAs are mainly involved in processes related to signal transduction, regulation of mRNA transcription and gene expression, synapse regulation, immune response, angiogenesis and vascular development. These results suggest that miRNAs could play an important role at the tick-host interface, providing new insights into this complex relationship that may contribute to a more precise selection of tick molecules for the development of therapeutic and immune strategies to control tick infestations and tick-borne pathogens.